Technology and the Third World : the issues and the role for Canada - McKinley, Kathryn; Young, Roger (Ottawa : North-South Institute, 1979)
This publication has been presented as a series of research and discussion papers to stimulate extensive discussion in Canada and abroad of a wide range of topics pertaining to Canada's relations with the developing world.
Includes bibliographical references.
osa;18/05/17
Loans
Keywords: Technical assistance, Canadian; Technology and state; Technology; Science; Technology transfer